Cost-effectiveness of an 8-week supervised education and exercise therapy programme for knee and hip osteoarthritis: a pre–post analysis of 16 255 patients participating in Good Life with osteoArthritis in Denmark (GLA:D) - Ewa M Roos; Søren T Skou; Rikke Ibsen; Jakob Kjellberg; Dorte T Grønne (BMJ Open)
Objectives To evaluate 1-year cost-effectiveness of an 8-week supervised education and exercise programme delivered in primary care to patients with symptomatic knee or hip osteoarthritis (OA).Design A registry-based pre–post study linking patient-level data from the Good Life with osteoArthritis in Denmark (GLA:D) registry to national registries in Denmark.Setting and participants 16 255 patients with symptomatic knee or hip OA attending GLA:D.Intervention GLA:D is a structured supervised patient education and exercise programme delivered by certified physiotherapists and implemented in Denmark.Outcome measures Adjusted healthcare costs per Quality-Adjusted Life Year (QALY) gained from baseline to 1 year (ratio of change in healthcare costs to change in EuroQoL 5-Dimensions 5-Level questionnaire (EQ-5D)). All adjusted measures were estimated using a generalised estimating equation gamma regression model for repeated measures. Missing data on EQ-5D were imputed with Multiple Imputations (3 months: 23%; 1 year: 39 %).Results Adjusted change in healthcare cost was 298€ (95% CI: 206 to 419) and 640€ (95% CI: 400 to 1009) and change in EQ-5D was 0.035 (95% CI: 0.033 to 0.037) and 0.028 (95% CI: 0.025 to 0.032) for knee and hip patients, respectively. Hence estimated adjusted healthcare costs per QALY gained was 8497€ (95% CI: 6242 to 11 324) for knee and 22 568€ (95% CI: 16 000 to 31 531) for hip patients. In patients with high compliance, the adjusted healthcare costs per QALY gained was 5438€ (95% CI: 2758 to 9231) for knee and 17 330€ (95% CI: 10 041 to 29 364) for hip patients. Healthcare costs per QALY were below conventional thresholds for willingness-to-pay at 22 804€ (20 000£) and 43 979€ (US$50 000), except the upper limit of the 95% CI for hip patients which was in between the two thresholds.Conclusions A structured 8-week supervised education and exercise programme delivered in primary care was cost-effective at 1 year in patients with knee or hip OA supporting large-scale implementation in clinical practice.